Architecture of the MEAN stack exploring the new web dev tools : MongoDB, ExpressJS, AngularJS, NodeJS - Davis, Scott 1971- (O'Reilly Media, 2015)
"Discover how the MEAN development stack--MongoDB, ExpressJS, AngularJS, NodeJS--changes the architecture and semantics of building a web application. In this incisive video course, you'll learn how NodeJS serves as the MEAN stack platform, ExpressJS acts as the web server, AngularJS delivers the user interface, and MongoDB provides persistence."--Resource description page.
Title from title screen (viewed May 11, 2015). - Date of publication taken from resource description page
Keywords: MongoDB; Node.js; Web applications -- Development; JavaScript (Computer program language); EXPRESS (Computer program language); Software architecture; Applications Web; Développement; JavaScript (Langage de programmation); EXPRESS (Langage de programmation); Architecture logicielle